Evaluasi Efek Penerapan Jambi University English Language Test (JUELT) Computer Based Test (CBT) Online Terhadap Resistensi Pengguna (Studi Kasus: UPT Bahasa Universitas Jambi) - faningfitriani (Prodi Sistem Informasi FST Universitas Jambi, 2021)
JUELT CBT Online is an english test service intended for students. The implementation of the information system is a change from a manual system to an online system. There are several obstacles faced in the implementation of information systems in an organization, one of which is user resistance. Resistance can be in the form of an individual's tendency to resist change and try to maintain the status and comfort of work as they have previously obtained. The purpose of this study is to determine the factors that influence and do not affect user resistance to the implementation of JUELT CBT Online at Jambi University. The population in this study were students at the University of Jambi. The sample size is 100, which is taken by non-probability sampling technique and analysis methods using sem-pls. The results of this study indicate that of the 8 variables used, there are 5 accepted hypotheses, namely Change in Job content (CJC) has a direct effect on Usability issues and resistance to technology (UIRT), Lack of communication between top management and end user (LCMU) has a direct effect. on User Expectation (UE), Lack of user involvement in the development process (LUID) has a direct effect on User Expectation (UE), Usability issues and resistance to technology (UIRT) have a direct effect on Increased effort (IE), Increased effort (IE) ) has a direct effect on Resistance due to change (RDC), while the 3 rejected hypotheses, namely Lack of Education and User training (LUET) have no direct effect on Usability issues and resistance to technology (UIRT), Change in Job content (CJC) has no effect directly on Increased effort (IE), and User Expectation (UE) has no direct effect on Resistance due to change (RDC).